LESSONS IN SCIENCE SAFETY WITH MAX AXIOM SUPER SCIENTIST : An Augmented Reading Science Experience - Lemke, Donald B.; Adamson, Thomas H., 1970-; Harbo, Christopher L.; Smith, Tod; Anderson, Bill; Browne, Ronald, Dr. (North Mankato, Minnesota : Capstone Press, 2019)
"Follow along carefully as Max Axiom teaches the most important lesson in science: Safety! From hot tips for using hot plates to cool answers to burning questions, young readers will hone their super safety skills. Download the free Capstone 4D app for an augmented reality experience that goes beyond the printed page. Videos, writing prompts, discussion questions, and hands-on activities make this updated edition come alive and keep your collection current."--
Includes index
This is 4D book
Age 8-14.
Keywords: Science -- Experiments -- Safety measures -- Juvenile literature; Laboratories -- Safety measures -- Juvenile literature; Safety education -- Juvenile literature